Knowledge map of self-reported outcomes in patients with prostate cancer: a bibliometric analysis (2014-2023) - Qin, Qiuxia; Liu, Juan; Zeng, Na; Xie, Xiaoqin; Yang, Fan (Frontiers in Urology, 2025)
ObjectiveTo analyze the related literature of self-reported outcomes of prostate cancer patients using bibliometric methods, and explore the research status and development trend in this field.MethodsThe literature related to self-reported outcomes of prostate cancer was searched in Web of Science core database. The literature on prostate cancer self-reported outcomes was visualized using VOSviewer, CiteSpace and R software packages.ResultsA total of 1119 relevant literatures were retrieved. Annual output consistently exceeded 100 articles since 2018, peaking at 161 in 2022. The U.S. (47.2%) and U.K. (21.5%) contributed 68.7% of publications. The University of Michigan emerged as the most productive institution. Collaborative networks showed strong U.S.-European ties, while Asian engagement intensified post-2020.The journal International Journal of Radiation Oncology Biology Physics (n=69) published most papers, whereas Journal of Clinical Oncology (n=48, citations=1,412) was most influential. Dual-map analysis revealed frequent citations from molecular/biology journals to clinical medicine literature. Barocas D.A., Cooperberg M.R., Koyama T., and Chen R.C. (21 publications each) were top producers. Ethan Basch (259 co-citations) was the most cited scholar. The EPIC scale development study (Wei et al., 2000) was the most co-cited reference. Key citation bursts included Taneja’s long-term outcomes study (2013-2018) and the CHHiP radiotherapy trial (2018-2021). “Quality of life” (181 occurrences) dominated keyword analysis, followed by “radiation therapy” and “prostatectomy.” Five thematic clusters emerged: radiotherapy with a blue cluster, prostatectomy with a green cluster, daily management with a red cluster, research methods with a yellow cluster and scale development with a purple cluster. Qualitative methods gained prominence after 2020, while exercise and radiotherapy remained sustained intervention focuses.ConclusionsThe reported outcomes of patients with prostate cancer have continued to receive attention in the past 10 years. In this study, three recognized bibliometric software were used for the first time to analyze the related studies on the reported outcomes of patients with prostate cancer, so as to provide reference and direction for future research.